PEMBERDAYAAN GURU TK AISYIYAH SURAKARTA DALAM PENDAMPINGAN PSIKOLOGIS PASKA BENCANA - Gati, Norman Wijaya; Joko Sri Pujiyanto; M. Zainul Arifin (P3M Universitas Aisyiyah Surakarta, 2024)
Indonesia is one of the countries that has a geographical location that is adequate for frequent disasters. Indonesia is located in a series of tectonic plates Australia, Pacific Eurasia and the Philippines. This geographical location allows for collisions between tectonic plates. This collision will cause natural disasters. Disasters are events that cannot be predicted and will have physical and psychological impacts. Disasters are stressors. Stressors that occur repeatedly will increase the potential for individuals to experience anxiety problems to depression. Increased anxiety can be experienced by all ages, therefore psychological assistance is needed after a disaster. This psychological assistance is in the form of activities to overcome anxiety and depression and reduce tension due to repeated exposure to stressors. Psychological assistance can be carried out by nurses and cadres. In this case, this PKM activity aims to improve the ability of PAUD and TK teachers in Surakarta City to assist in psychological assistance after a disaster. The method of service used is a 2-day workshop with the first day divided into in-depth theory and the second day in the form of direct simulation of psychological assistance after a disaster. The results of this service found an increase in the level of knowledge about psychological first aid after a disaster by 15.8%.